The Sermon by B. Hoadly on the “Happiness of the Present Establishment” of England (1707) - Veronika V. Vysokova; Ekaterina A. Solov'eva (Historia provinciae: журнал региональной истории, 2024)
The article examines the process of formation of the origins of Whig ideology using the example of Benjamin Hoadly’s sermon The Happiness of the Present Establishment, and the Unhappiness of Absolute Monarchy. In the struggle between Tories and Whigs on the main issue of the political agenda in Britain at the beginning of the 18th century – the succession to the throne – the foundations for the Whigs’ ideological program were first laid. The Stuart dynasty was divided by the events of the Glorious Revolution of 1688–89. The exiled Stuarts remained a real threat to the reign of Queen Anne Stuart (1701–14). Of particular interest in this context is the analysis of the circumstances of the involvement of the clergy in the ideological and political struggle in Britain in the situation of an acute internal political crisis during the period of its participation in the War of the Spanish Succession (1701–14). The significance of addressing the sermon genre is determined by the fact that along with newspaper articles, sermons began to be widely published in the period under consideration. The authors of the article characterize the personality of Benjamin Hoadly, an Anglican priest, the author of the sermon under study, as a political activist who skillfully linked biblical stories with the current political agenda. The main storyline of the sermon is based on the story of the Israeli kings Saul and David from the Book of Samuel of the Old Testament. The sermon focuses on the discussion of the issue of the “happy establishment,” the Kingdom of David, which, according to Hoadly, corresponded to the Kingdom of England in the early 18th century. The latter, in its turn, is contrasted with the Kingdom of Saul, the regime of an absolute monarchy, namely France. The goal, main idea, and system of argumentation in Hoadly’s sermon were intended to enlist the support of the reigning Queen Anne Stuart during the election campaign for the House of Commons in 1707–08. The sermon declares her reign the happiest for the Kingdom of England and contrasts it with absolutist France. The text of B. Hoadly’s sermon with minor abridgements translated by the authors of the article is published in Russian for the first time.